288OMolecular profiling and treatment patterns of advanced salivary gland cancers in head and neck region. (24th November 2019) - Talreja, V; Patil, V M; Noronha, V; Joshi, A; Menon, N; Chougule, A; Menon, M; Mittal, N; Prabhash, K
Abstract: Background: Advanced salivary gland neoplasm have variable natural history. The goal of systemic treatment is palliation however no clear evidence regarding when and to whom it needs to be administered.The objective of this study was to determine the molecular profile of malignant salivary gland tumors and to evaluate the impact of systemic therapy.This was a retrospective cohort study. Methods: Head and Neck Medical Oncology outpatient department maintains a prospective chemotherapy database of patients planned for any form of systemic therapy. Adult patients (Age > or = 18 years) with (ECOG PS) 0-3 histologically proven salivary gland malignancy treated between January 2010- September 2018 at the host institute.Data regarding demographics, baseline characteristics, tumor details, staging details, treatment details, outcome details expression of ER, PR, AR and HER-2 Neu status was extracted.The procedure for performing IHC, interpreting, and quality assurance is already published.Molecular profilingSnapshot profiling was performed using Multiplex polymerase chain reaction (PCR) followed by multiplex base extension assay utilizing the SNaPshot TM methodology. It consists of a combination of real time PCR looking for 21 hotspot mutation sites in nine cancer genes: (EGFR, HER2, KRAS, NRAS, PIK3CA, BRAF, MEK1, PTEN, AKT1-). Results: Out of the 69 evaluable patients, 55% (n = 38) had actionable target. Androgen Receptor (AR) expression was present in majority of patients (n = 23, 34%), with it alone being expressed in 17% (n = 12) of patients, and along with other actionable targets in the other. 60 (87%) patients received systemic therapy either in form of chemotherapy (35, 58.3%) or targeted therapy (25, 41.7%). The strategy of observation in asymptomatic status lead to an median OS of 32.27 (3.03-NA) similar to patients receiving systemic therapy (p = 0.992). In patients with visceral crisis, the median OS was higher in patients receiving chemotherapy than targeted therapy (19.07 (14.20-23.8) versus 6.07 (2.23-NA), p < 0.001).The median follow up was 42.1(95% CI 36.5-51.7) months. Conclusions: Actionable targets are seen in salivary gland tumors and treatment strategies should be based on these and symptomatic status. Legal entity responsible for the study: Tata Memorial Hospital Mumbai. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.